Effects Of Teachers’ Questioning Strategies On Students’ Achievement In Social Studies In Obio-Akpor Local Government Area Of Rivers State, Nigeria - Opara, Ijeoma Margaret; Uma, Ajike Afor (Advances in Social Sciences Research Journal, 2020)
The study investigated the effects of teachers’ questioning strategies on students’ achievement in Social Studies in Obio-Akpor Local Government Area of Rivers State, Nigeria. Four research questions and four null hypotheses guided the study. The study adopted quasi-experimental research design. A sample of one hundred and twenty (120) male and female JS3 students from three (3) intact classes A, B, and C in the ratio of 40:40:40 respectively using stratified and purposive sampling techniques were used for the study. The instrument used for the study was titled Social Studies Achievement Test (SSAT). The instrument was validated by subject specialists and measurement and evaluation experts based on content and face validities. The reliability of the instrument was determined using Kuder-Richardson 20 formula and the reliability coefficient obtained was 0.87. Mean and standard deviation were used to answer the research questions while t-test and Analysis of Variance (ANOVA) were used to test the hypotheses at 0.05 alpha level. The result revealed that convergent and divergent questioning strategies significantly had effects on students achievement in Social Studies, while gender had no significant effect. Based on these findings, it was recommended among others that teachers should pay more attention to their questioning strategies because they are frequently used tools and the way to good teaching.